Inspection of Endothelial Nitric Oxide Synthase Gene Polymorphism in Patients With Henoch Schönlein Purpura - Makbule Nihan SOMUNCU,; Mahmut Selman YILDIRIM,; Ayşegül ZAMANİ,; Harun PERU, (Archives of Rheumatology, 2014)
Objectives: This study aims to investigate the effect of Glu298Asp polymorphism, which is observed at endothelial nitric oxide synthase isoform particularly, having a significant impact on endothelial functions of nitric oxide synthase gene and on vascular system in patients with Henoch Schönlein purpura (HSP). Patients and methods: Ninety-five patients who were diagnosed with HSP and 93 healthy controls without any previous vascular disease, hypertension and other cardiovascular diseases were included in this study. The patient group was compared with the controls for Glu298Asp genotype and allele frequencies. The patients were classified according to the clinical complications and were compared with controls and also each other for allele and genotype frequencies. Real-time polymerase chain reaction and LightCycler“ 2.0 system were used. Results: There was no statistically significant difference in the genotype frequencies between the HSP patients and healthy controls. No significant differences in Glu298Asp gene polymorphism among the patient groups were observed. However, polymorphism had an significant effect on patients with all involvements statistically (PTT=0.001, PGG=0.000). Conclusion: We conclude that Glu298Asp polymorphism has no effect on the development of HSP vasculitis; however, it may have an impact on the clinical progress of the existing disease.